Case Report: Rare Presentation of Mixed Germ Cell Tumor in an Infant - Talluri, Sriharsha; Goedde, Michael A.; Coventry, Susan; Rosenberg, Eran; Canalichio, Katie L.; Peppas, Dennis; White, Jeffrey T. (Frontiers in Pediatrics, 2021)
The estimated incidence of pediatric testis tumor is 0.5 to 2.0 per 100,000 children, accounting for 1%–2% of all pediatric tumors. Mixed germ cell tumors (MGCT) in prepubertal males are exceedingly rare, with only one previous case in the literature. We report a case of a MGCT in an infant. For prepubertal males, GCTs typically present with a painless scrotal mass, though trauma, testis torsion and hydrocele are also common presentations. Similar to such tumors in postpubertal males, ultrasonography, computed tomography, and tumor markers are integral to determine the best treatment. With prudent management, these patients tend to have favorable prognoses.